Current Legume Consumption in U.S. Adults: Results from the National Health and Nutrition Examination Survey (NHANES) 2011–2014 (P04-135-19). (13th June 2019) - Perera, Thushanthi; Takata, Yumie; Bobe, Gerd
Abstract: Objectives: The objective of this study was to evaluate current legume consumption in U.S. adults by using cross-sectional data from the 2011–12 and 2013–14-year cycles of NHANES Methods: Participants were grouped into non-legume consumers and consumers, which were further grouped into low mature legume consumers (<37.5 g/d, which are the dietary recommendations for mature legume consumption), marginal mature legume consumption (37.5–87.49 g/d, the latter being the cut-off point demonstrating nutritional and disease prevention benefits), and disease prevention mature legume consumption (≥ 87.5 g/d legume consumption). Groups were compared using a t-test (for comparison of legume consumers vs. non-consumers) or generalized least-squared means (for comparison among legume consumer groups) for continuous data and a chi-square test for categorical data. All tests were two-sided. Significance of group differences was determined to be at P ≤ 0.05. Results: Legume consumption frequency in U.S. adults was low and showed a downward trend from 2011 to 2014 of 18.5% to 13.7% on a given day. The downward trend is primarily due to a decrease in dry bean consumption from 10.0% to 6.5%. The primary legume groups consumed were dry beans and green legumes; chickpeas and lentils were consumed by about 1% of participants at a given day. Legumes were mainly consumed as side or main dish (both primarily dry beans and green legumes) with a declining trend over time for using legumes as soup and main dish. 2.2% (2011–2012) and 1.8% (2013–2014) of NHANES participants ate at least 1 cup/d of mature legumes, 7.1% (2011–2012) and 5.3% (2013–2014) at least 0.5 cup/d of mature legumes, and 14.0% (2011–2012) and 10.7% (2013–2014) at least 37.5 g/d of mature legumes during the 2 surveying days after adjusting for caloric intake. Conclusions: Legume consumption declined rather than increased in U.S. adults, warranting improved communication about the disease prevention benefits of regular legume consumption. Funding Sources: None.